Influence of Sodium and Potassium Ions on Acid Production by Washed Cells of Streptococcus mutans Ingbritt and Streptococcus sanguis NCTC 7865 Grown in a Chemostat - Marsh, Philip D. (American Society for Microbiology (ASM), 1982)
A comparison was made of acid production by cells of Streptococcus mutans Ingbritt and S. sanguis NCTC 7865 that had been washed twice and incubated in different concentrations of sodium and potassium ions. Organisms were grown under defined conditions in a chemostat under both glucose limitation and glucose excess conditions at a dilution rate of 0.1 h(−1) (mean generation time, 6.9 h). Acid production after a pulse of glucose, sucrose, and fructose was measured by pH fall experiments and as a rate at pH 7.0. S. mutans produced more acid than S. sanguis as measured by either criterion, although statistically faster rates of acid production and lower terminal pH values were obtained when cells of both species were suspended in KCl rather than in NaCl, with 200 mM KCl resulting in the lowest terminal pH in pH fall experiments. Sodium ions inhibited acid production: 183 mM NaCl reduced the glycolytic rates of S. mutans and S. sanguis metabolizing glucose at pH 7.0 in 135 mM KCl by 39 and 33%, respectively. The most pronounced stimulatory effect of potassium on acid production was by washed cells of S. sanguis that had been grown under arginine and under phosphate limitation. The pH fell by a further 0.86 and 1.21 pH units, respectively, and to below the critical pH for enamel demineralization when these cells were metabolizing glucose in 135 mM KCl compared with the same concentration of NaCl. This enhancement of acid production was not due to potassium translocation, as had been suggested previously, because no movement of potassium ions across the cell membrane could be detected. An alternative explanation is proposed in which sodium ions are excluded from the cell at the expense of membrane energy, i.e., the proton motive force, which could otherwise be used for the transport of sugars.